Is it financially beneficial for hospitals to prevent nosocomial infections? - Shmuel Benenson; Matan J. Cohen; Carmela Schwartz; Michael Revva; Allon E. Moses; Phillip D. Levin (BMC, 2020)
Abstract Background Financial incentives represent a potential mechanism to encourage infection prevention by hospitals. In order to characterize the place of financial incentives, we investigated resource utilization and cost associated with hospital-acquired infections (HAI) and assessed the relative financial burden for hospital and insurer according to reimbursement policies. Methods We conducted a prospective matched case-control study over 18 months in a tertiary university medical center. Patients with central-line associated blood-stream infections (CLABSI), Clostridium difficile infection (CDI) or surgical site infections (SSI) were each matched to three control patients. Resource utilization, costs and reimbursement (per diem for CLABSI and CDI, diagnosis related group (DRG) reimbursement for SSI) were compared between patients and controls, from both the hospital and insurer perspective. Results HAIs were associated with increased resource consumption (more blood tests, imaging, antibiotic days, hospital days etc.). Direct costs were higher for cases vs. controls (CLABSI: $6400 vs. $2376 (p < 0.001), CDI: $1357 vs $733 (p = 0.047) and SSI: $6761 vs. $5860 (p < 0.001)). However as admissions were longer following CLABSI and CDI, costs per-day were non-significantly different (USD/day, cases vs. controls: CLABSI, 601 vs. 719, (p = 0.63); CDI, 101 vs. 93 (p = 0.5)). For CLABSI and CDI, reimbursement was per-diem and thus the financial burden ($14,608 and $5430 respectively) rested on the insurer, not the hospital. For SSI, as reimbursement was per procedure, costs rested primarily on the hospital rather than the insurer. Conclusion Nosocomial infections are associated with both increased resource utilization and increased length of stay. Reimbursement strategy (per diem vs DRG) is the principal parameter affecting financial incentives to prevent hospital acquired infections and depends on the payer perspective. In the Israeli health care system, financial incentives are unlikely to represent a significant consideration in the prevention of CLABSI and CDI.